2020
DOI: 10.1029/2019je006369
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Small‐Scale Waves and Wave‐Like Phenomena in Jupiter's Atmosphere Detected by JunoCam

Abstract: In the first 20 orbits of the Juno spacecraft around Jupiter, we have identified a variety of wave‐like features in images made by its public‐outreach camera, JunoCam. Because of Juno's unprecedented and repeated proximity to Jupiter's cloud tops during its close approaches, JunoCam has detected more wave structures than any previous surveys. Most of the waves appear in long wave packets, oriented east‐west and populated by narrow wave crests. Spacing between crests were measured as small as ~30 km, shorter th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Since the EMF eddies are accelerating both the eastward and westward jets, it is natural to assume that the phase speeds c of the waves are similarly bounded by the jet speeds. Most of the mesoscale waves, which have wavelengths around 300 km, are inertia-gravity waves ( Orton et al, 2020 ), and they satisfy this criterion—their phase speeds are <50% and often <10% of the zonal flow speeds, regardless of direction ( Arregi et al, 2009 ; Hunt & Muller, 1979 ; Orton et al, 2020 ; Simon et al, 2015 ). So, we choose a reference frame that has eastward jets on the poleward sides of the zones and westward jets on their equatorward sides, and we assume c = 0 in that frame.…”
Section: Introductionmentioning
confidence: 99%
“…Since the EMF eddies are accelerating both the eastward and westward jets, it is natural to assume that the phase speeds c of the waves are similarly bounded by the jet speeds. Most of the mesoscale waves, which have wavelengths around 300 km, are inertia-gravity waves ( Orton et al, 2020 ), and they satisfy this criterion—their phase speeds are <50% and often <10% of the zonal flow speeds, regardless of direction ( Arregi et al, 2009 ; Hunt & Muller, 1979 ; Orton et al, 2020 ; Simon et al, 2015 ). So, we choose a reference frame that has eastward jets on the poleward sides of the zones and westward jets on their equatorward sides, and we assume c = 0 in that frame.…”
Section: Introductionmentioning
confidence: 99%
“… 2009 ) and Juno imaging (Orton et al. 2020 ), and interpreted to be gravity (i.e., buoyancy waves in a stably-stratified atmosphere) or inertia-gravity waves (i.e., sensing the Coriolis effect). Mesoscale waves modulating cloud opacity and reflectivity, often found in regions of cyclogenesis, have been observed by the Hubble Space Telescope (HST, Fig.…”
Section: Jupiter Scientific Objectivesmentioning
confidence: 99%
“…Evidence shows vigorous wave activities in Jupiter's atmosphere, especially in the equatorial region (e.g., Rogers & Mettig 2008;Asay-Davis et al 2011;Simon-Miller et al 2012). Most of these wave features appear within ±5°of latitude (Simon-Miller et al 2015;Orton et al 2020), and they exhibit diversity and complexity with various zonal wavenumbers, including waves with wavenumbers between 17 and 70 (Harrington et al 1996;Cosentino et al 2017a). Simon-Miller et al (2012 showed that these waves consist of wavenumbers 75 and and have a phase speed of 101 ± 3 m s −1 , which are likely inertia-gravity waves.…”
Section: Introductionmentioning
confidence: 99%